Introduction: The Modernization of Financial Services Legislation - Laurence H. Meyer (Washington University Law Quarterly, 1999)
Today, I would like to talk to you about something that has devoured much of my time at the Fed and has also taught me to listen more closely to the nuances of government-speak—financial modernization. The issues are real and affect all of us in our daily lives.
Keywords: Banking industry; Banking law; Deregulation; Financial institutions; Financial services; Securities law